How well has environmental and social protection been ensured for small farmers and fisherfolk? Sustainable development of Philippine agriculture and fisheries - Maria Corazon M. Ebarvia (Philippine Institute for Development Studies (PIDS), 2022)
Transforming Philippine agriculture and fisheries (AF) into a dynamic, high-growth sector is essential to poverty reduction, food security, and inclusive economic prosperity. However, unsustainable AF practices have impacts on the environment and climate, and at the same time, ecosystem degradation and climate change impact the productivity and sustainability of the AF sector, with disastrous consequences on food security, income, and livelihoods, especially of small-scale farmers and fishers. Agriculture and fisheries rely on natural capital and are both providers and consumers of ecosystem services, and at the same time pose a threat to nature. This report describes the range of pressures affecting the state of the AF sector, and the response measures being undertaken. Integrating environmental sustainability and climate resilience in AF development and modernization plans has emerged as a necessity in policy and practice. Interventions and priorities need to be defined according to local contexts but within the integrated river basin, coastal zone, and marine area framework. Various practices in ecosystem-based management in agriculture and fisheries exist, and supported by key policies, but sectoral and silo approaches still dominate. The challenge for policymaking is to facilitate dialogue, knowledgesharing, and collaboration, create the market and/or regulatory conditions to incentivize uptake of sustainable practices, and help farmers and fisherfolk access the necessary inputs, financing, and technologies, and acquire the skills that will allow them to follow the economically feasible, environmentally sound, and societally desired path.
Keywords: 330; sustainable development; ecosystem services; climate change; agroecosystems; soil; fisheries; aquaculture; overfishing; IUU fishing; pollution